2020
DOI: 10.1523/jneurosci.0810-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization-Dependent C-Raf Signaling Promotes Hyperexcitability and Reduces Opioid Sensitivity of Isolated Nociceptors after Spinal Cord Injury

Abstract: Chronic pain caused by spinal cord injury (SCI) is notoriously resistant to treatment, particularly by opioids. After SCI, DRG neurons show hyperactivity and chronic depolarization of resting membrane potential (RMP) that is maintained by cAMP signaling through PKA and EPAC. Importantly, SCI also reduces the negative regulation by Gai of adenylyl cyclase and its production of cAMP, independent of alterations in G protein-coupled receptors and/or G proteins. Opioid reduction of pain depends on coupling of opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…Spinal cord injury procedure Rat SCI surgeries (SCI group) were performed as previously described (Bedi et al, 2010;Bavencoffe et al, 2016;Berkey et al, 2020;Garza Carbajal et al, 2020). Animals were anesthetized with isoflurane (induction 4%-5%; maintenance 1%-2%, Covetrus) before a laminectomy at the vertebral T10 level was performed, followed by a dorsal contusive spinal impact (150 kilodyne, 1 s dwell time) using an Infinite Horizon Spinal Cord Impactor (Precision Systems and Instrumentation).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinal cord injury procedure Rat SCI surgeries (SCI group) were performed as previously described (Bedi et al, 2010;Bavencoffe et al, 2016;Berkey et al, 2020;Garza Carbajal et al, 2020). Animals were anesthetized with isoflurane (induction 4%-5%; maintenance 1%-2%, Covetrus) before a laminectomy at the vertebral T10 level was performed, followed by a dorsal contusive spinal impact (150 kilodyne, 1 s dwell time) using an Infinite Horizon Spinal Cord Impactor (Precision Systems and Instrumentation).…”
Section: Animalsmentioning
confidence: 99%
“…FIBSI was written using the Anaconda (version 2019.7.0.0, Anaconda) distribution of Python (version 3.5.2) with dependencies on the NumPy and matplotlib.pyplot libraries (Cassidy et al, 2020). The FIBSI program incorporates the previously published algorithm used to analyze DSFs in our prior publications (Odem et al, 2018;Berkey et al, 2020;Garza Carbajal et al, 2020;Lopez et al, 2021;North et al, 2022). FIBSI uses the Ramer-Douglas-Peucker algorithm to detect DSFs, which were obtained from 30 s recordings sampled at 10 kHz with PatchMaster version 2x90.1 (HEKA Elektronik) and filtered with a 10 kHz Bessel filter.…”
Section: Measurement Of Dsfs Of Membrane Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, isolation of primary cardiomyocytes is very difficult, and H9C2 cells are a generally accepted model for evaluation of cardiomyocyte biochemistry. Since H-89 has been demonstrated to effectively inhibit PKA phosphorylation [60][61][62][63], the expression levels of PKA and p-PKA were not evaluated in this study to confirm that PKA activity was inhibited. is study showed that the occurrence of arrhythmia after ischemia was closely related to phosphorylation of RyR2 (Ser2808) and RyR2 (Ser2814) by CaMKII, which promoted dissociation of the FKBP12.6-RyR2 complex, and increased intracellular Ca 2+ content.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic activity can originate from axons, in particular early after injury, but it can also emerge from the DRG soma (Amir et al, 2005). This likely happens due to changes in expression of ion channels in the DRG neuronal soma (Devor, 2006), or due to signaling events that cause the neuron to generate ectopic action potentials and instability in the resting membrane potential (Devor and Yarom, 2002; Odem et al, 2018; Garza Carbajal et al, 2020; Laumet et al, 2020; Lopez et al, 2021). Our previous work clearly showed that human DRG neuron somata from neuropathic pain patients could display ectopic activity, even after surgical removal and culturing (North et al, 2019).…”
Section: Discussionmentioning
confidence: 99%